Communication—Accessing Stability of Oxidase-Based Biosensors via Stabilizing the Advanced H2O2 Transducer. Issue 5 (1st January 2017) - Karpova, Elena V.; Karyakina, Elena E.; Karyakin, Arkady A.
Abstract : Operational stability of biosensors is of particular importance especially for wearable devices. Prussian Blue (PB) based advanced hydrogen peroxide transducer, 1000 times more active and selective than platinum, is deposited onto screen-printed structures and stabilized with nickel hexacyanoferrate (NiHCF), both in open circuit mode. Operational stability of PB-NiHCF bilayer based biosensors and labile lactate oxidase is significantly improved in terms of twice longer half inactivation and ≈3.5 times lower inactivation constant. The dynamic range of PB-NiHCF based biosensors is similar to it for conventional PB based ones, which allows using the former for similar purposes drastically improving their performance characteristics.